Development of viscosity models of concentrated suspensions: Contribution of particle-size and shape indices. (5th September 2022) - Youness, Dima; Yahia, Ammar; Tagnit-Hamou, Arezki
Highlights: Introducing combined particle-size and shape parameters in determining the relative viscosity. The intrinsic viscosity, wet packing, and void content of systems are predicted using Carr measurements. Flowability parameters are varying by their dry packing-cohesion and morphology. Dynamic parameter angle of fall is a wet dispersion indicator for particles. Abstract: Blending cementitious powders marks multiple morphological features which dictate the rheology of cement-based suspensions. Models, whether theoretical or empirical, unveiled the convolution in describing the consequence of particles' morphology on the rheology of cement-based suspensions. The viscosity of various cement suspensions designed with different liquid-to-binder ratios was examined. Models, for instance, Krieger–Dougherty and Mooney, were implemented to foresee the relative viscosity of the employed suspensions in terms of the coupled physical properties and dry relative solid fraction. The coefficient kE and intrinsic viscosity (η) are in good agreement with particle-size indices, including fineness index (SSA × Gs ) and particle-size ratio (d50 2 /SSA). In addition, the current models were adjusted with a focus on new coupled-physical properties, including static (αR  × αS ), dynamic (αF  × cohesion), and total flowability (ftotal ) indices. This resulted in significant improvement in the precision of determining the viscosity of concentrated cement-based suspensions.